Common mental disorders of health care workers in Bahia state - Saulo Vasconcelos Rocha; Aline Rodrigues Barbosa; Tania Maria de Araújo (Universidade Estadual de Maringá, 2018)
To estimate the prevalence of common mental disorders (CMDs) and check the characteristic symptoms of CMDs in workers in the health sector.Cross-sectional study conducted in four municipalities in the state of Bahia. The study included 2,684 workers (21.6% men and 78.4% women), with ages ranging from 19 to 82 years (38.38 ± 10.1). CMDs were identified through the Self-Reporting Questionnaire-SRQ-20. Sociodemographic and occupational data were investigated and described using simple frequency and the calculation of ratios, and their respective 95% confidence intervals. The association between CMD and the explanatory variables (according to sex) were assessed using regression gross and adjusted Poisson regression analysis. The prevalence of CMD was more pronounced among women (22.7; 95% CI: 20.8 to 24.5%). The most reported symptom among men (38%) and women (50%) was feeling nervous, tense or worried. The prevalence of TMC was more prevalent among women and workers gazetted .The prevalence of CMD among health workers is high and differed between the sexes and dependence employment bond.